Low-sodium versus standard-sodium peritoneal dialysis solution in hypertensive patients: a randomized controlled trial - Rutkowski, Bolesław; Tam, Paul; van der Sande, Frank M.; Vychytil, Andreas; Schwenger, Vedat; Himmele, Rainer; Gauly, Adelheid (American journal of kidney diseases, 2016)
Peritoneal dialysis (PD) solutions with reduced sodium content may have advantages for hypertensive patients; however, they have lower osmolarity and solvent drag, so the achieved Kt/Vurea may be lower. Furthermore, the increased transperitoneal membrane sodium gradient can influence sodium balance with consequences for blood pressure (BP) control.